A qualitative study to understand the barriers and enablers of access to diabetic screening services in Nigeria - Ozioko, Nnenna; Kamalakannan, Sureshkumar (International Journal Of Community Medicine And Public Health, 2024)
Nigeria in working to redefine its health care system's approach to diabetic retinopathy (DR) screening services needs to reduce obstacles and highlight the enablers to services provision. Due to the increased prevalence of diabetes, this has become increasingly necessary. A qualitative study examining the perceptions, practices, and experiences of Nigerian DR healthcare practitioners (HCPs) in relation to the facilitators and barriers of access to DR screening services. Mode of participant recruitment was on-line through e-mails by using snowballing method. In-depth interviews were used to acquire information from 6 DR HCPs (all ophthalmologists) at three eye centers in the three geo-political areas of Nigeria and at international center for eye health (ICEH) in London via on-line Microsoft teams. Thematic analysis was used for data analysis and all the steps applied to the data analysis process. Non-systematic screening, poverty, poor transport systems, insecurity, and poor motivation are key barriers to DR screening access in Nigeria while enablers include government participation through subsidized costs and remuneration of workers. Screening in communities, and using low-cost techniques are key to enable access. Other enablers include collaboration and integration between endocrinology and ocular units in terms of referrals, information sharing, use of intermediary carers, technology, man-power and health resource provision including low- cost services. A dearth of personnel, screening technologies, and resources, have an impact on the effectiveness of the DR screening services in Nigeria as well as social and individual factors, such as the cost of the services and national insecurity.